Spatiotemporal evolution patterns and driving factors of arable land in Huaihai Economic Zone, China - Wang, Peijun; Lin, Ziqi; Wang, Jing; Yang, Yali; Mu, Shouguo (Frontiers in Environmental Science, 2023)
The Huaihai Economic Zone (HEZ) has excellent topographic and climatic conditions and is recognized as one of China’s major grain production areas. Identifying the spatiotemporal evolution patterns of arable land and the driving factors can offer valuable insights for protecting arable land, optimizing land use layout, and developing ecological economics in HEZ. In this paper, we analyze the spatiotemporal evolution patterns using spatial autocorrelation, land use transfer matrix, and kernel density calculations and investigate the driving factors of arable land evolution with Geodetector. The results show the following trends in the distribution of arable land within the HEZ: 1) The kernel density distribution of the arable land in HEZ remained relatively consistent from 2005 to 2020, but the density showed a downward trend over time. 2) The distribution of arable land in HEZ exhibited lower density in the Northeast and higher density in the Southwest, showing growth in the initial stage and subsequent declines in the intermediate and final phases. 3) A significant positive spatial correlation was observed in the distribution of arable land in HEZ. The main local cluster types were the “high-high” and “low-low” clusters, and their distribution characteristics were similar to the kernel density of arable land. 4) The change of arable land in HEZ between 2005 and 2020 was primarily driven by the conversion of land types, with a notable shift towards grassland and construction land 5) The main driving factors affecting the spatial distribution of arable land in HEZ included traffic accessibility, air temperature, precipitation, elevation, and slope. The secondary driving factors were land use and soil type. Over time, population and GDP have also evolved into significant driving factors. 6) The factors were bi-enhance after the interaction. In the future, all cities within HEZ should implement rigorous control measures to limit the expansion of arable land usage. Their primary focus should be on revitalizing existing construction land while strictly upholding the “compensation determines occupation” principle. They should also work to optimize the arrangement of arable land and give increased consideration to the interactive effects of traffic accessibility, population, and GDP to protect arable land in a more focused and effective manner.